Hate Crimes in America. - Abramovitz, Melissa (Special Reports Set 2., 2016)
Hate Crimes in America covers the history of crimes motivated by prejudice, examples of such incidents in the headlines today, and the ways in which communities are responding to these vicious acts. Aligned to Common Core Standards and correlated to state standards. Essential Library is an imprint of Abdo Publishing, a division of ABDO.